Economic Improvement through the Development of the Jamu Kiringan Yogyakarta Tourism Village: Peningkatan Ekonomi melalui Pengembangan Desa Wisata Jamu Kiringan Yogyakarta - Santosa*, Allicia Deana; Arifa, Nur Saudah Al; Masithoh, Robiul Fitri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
In Jamu Kiringan Tourism Village, Yogyakarta, a community service initiative addressed challenges in the herbal medicine industry, predominantly run by women. These challenges included limited raw material supply, insufficient product innovation, business licensing, halal certification, and digital marketing skills. To tackle these issues, the project employed strategies like providing and planting medical plant seeds to create independence for raw materials for herbal medicine sellers and as an additional herbal tourism attraction, product innovation training, guidance for obtaining halal certification and business permits, and digital marketing training utilizing free platforms such as Canva, Capcut, Klook, and Instagram. These measures aimed to bolster the village's herbal medicine sector, fostering innovation, quality assurance, and digital outreach, ultimately transforming it into a thriving Tourism Village.